(untitled) (Indian Journal of Traditional Knowledge (IJTK), 2023)
Jackfruit gets wasted to the tune of 5.8 million every year from 0.4-0.5 million jackfruit trees in Garo Hills due to lack of suitable infrastructure, limited scientific know-how regarding processing and storage, and restricted market access. The study aims to explore the status of jackfruit cultivation and utilisation of locally available jackfruit and to document the value addition practices followed by ethnic tribal communities in the Garo Hills of Meghalaya, India, to augment the standardisation of the sustainable value addition practices for the region. The study was conducted in all five districts of Garo Hills. Two blocks from each district were selected through a simple random sampling method. Twenty respondents from each selected block were selected through the snowball sampling method, thereby making a total of 200 respondents. Identification and documentation of ethnic value addition practices of tribal communities were done through Focused Group Discussion with the relevant stakeholders. Data were analysed with descriptive statistics and Duncan Multiple Range Test. The average wastage percentage was more than half of the jackfruit production in Garo Hills, as very few respondents (30.5%) engaged in value addition practices and due to negligible marketing of raw jackfruit (3970 kg). Identification, documentation of ethnic value addition practices, and their utilisation study provide a clear indication of the need for standardisation of these value addition practices through laboratory research to befit the local demand and outside market as well.